Construção e validação de tecnologia educativa para o cuidado de pessoas com estomia intestinal - Sena, Julliana Fernandes de (2017)
Living with the condition of having an oedematum causes several changes in the lives of people and their families. In this situation, difficulties arise in which often the patient and the family are not prepared to act in the face of the problem. All this generates the need to acquire new skills for self-care. Recognizing the importance of educational material with a focus on promoting the care of these patients, the present study aimed to construct an educational booklet and analyze the evidence of validation for the care of people with intestinal stomies. It is a methodological research of the type of development. To facilitate the understanding of the method, it was chosen to divide it into two stages: the first consisted of a literature review, a qualitative study with 30 people with intestinal stomies of the Specialized Center for Rehabilitation and Qualification of Rio Grande do Norte - CERHRN and the construction of the educational booklet, and the second consisted of validation of content, appearance and suitability of the material by nine expert judges, as well as validation as to its organization, writing style, appearance and motivation of the booklet with 25 people of the target population. The study was carried out at the CERHRN with the authorization of the board of directors and after approval of the Research Ethics Committee / UFRN under CAAE number 65942517.9.0000.5537. The Content Validity Index (CVI) was used to measure the judges' agreement on the representativeness of the items in relation to the study content. The evaluation instrument of the specialists contained items of evaluation of the Likert scale with four items. The index was calculated by means of the sum of the items marked "3" (appropriate) and "4" (fully appropriate) by the experts, divided by the total answers. As for the objectives of the booklet, all the judges validated the items, classifying them as "adequate" or "totally adequate", which gave an IVC of 1.00 for the proposed objectives. Regarding the structure and presentation of the booklet, it was considered validated, reaching a total CVI of 0.84. Regarding relevance, the total IVC was 0.97 and the general IVC of the educational booklet was 0.89, confirming the validation among the specialists in the area. After the suggestions made by the judges, the adequacy of the educational material was carried out, incorporating the suggestions, in order to meet the needs and expectations proposed. There was no negative response to items evaluated by the target audience. All items of the organization, writing style, appearance and motivation of the material were considered validated, as they reached a total agreement index of 99%. It is believed that the construction and validation of the educational booklet for the care of people with intestinal stomies can contribute positively to the adherence to the self-care practices of these people and also to the relatives and caregivers who perform or assist in this daily care. Subsequently, the educational material was sent to the Portuguese revision and to the printing press. The educational technology will be made available at the stomatal care facilities, but will only be provided to the patient who shows interest.